Michel Pastoureau and the history of visual communication. (February 2023) - Aiello, Giorgia; Van Leeuwen, Theo
Despite early and ongoing calls for a systematic engagement with history, social semiotics has largely emphasized research on the synchronic rather than diachronic dimensions of meaning-making. And while the 'instability' of semiotic practices (see Kress's Multimodality: A Social Semiotic Approach to Contemporary Communication, 2010) and the importance of semiotic change (see Van Leeuwen's Introducing Social Semiotics, 2005) have become key themes in semiotics, there is still a need for a dynamic approach to the study of visual and multimodal communication, focusing not only on describing how meaning-making resources and their uses are changing, but also on why they are changing. In this article, the authors focus on the importance of the work of medieval historian Michel Pastoureau for the social semiotic study of visual communication, highlighting that this work can help us further refine and even rethink key social semiotic concepts such as modes and media, provenance, and context. Pastoureau's work shows how we can make theoretical statements about instability, change and innovation more concrete and, ultimately, empirically based. His approach can also help us understand semiotic change and its relation to social and cultural (and also economic and technological) change more broadly, often with the aid of the (crucial) normative discourses that shape semiotic practices over time.